COMPARATIVE LITERATURE STUDY OF MOTIF DIFFERENCES IN RAGNAROK AND THE BOOK OF REVELATION - Wijianto, Agung (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2020)
This research aims to formulate the similarities and the differences of the death motif employed in Ragnarok and the Book of Revelation. Both of these stories use the same motif of death but with different portrayal and explanation of the death. The data used in this research are Ragnarok in the epic poem Voluspa and the Book of Revelation in the Bible. This research utilizes qualitative descriptive method and the theory of Genetic Structuralism to dissect the data. The steps are identifying the motifs, interpreting the motifs, and comparing the result. The findings show that even though the death motifs are prevalent in these two works, the themes riding the motifs are different. This happens because of the different collective subjects and the worldviews in which the works are created.